ANALISIS KUALITAS DAN KESESUAIAN TIU DAN TIK PADA BUKU TEKS BAHASA INDONESIA SISWA DAN GURU SMA KELAS XI TERHADAP KURIKULUM MERDEKA - Rosmawaty; Ayla Azura; Julia Cikita Sitorus; Nabila Nazzahra Putri Irwansyah; Naomi Nathanya Libe Gracella Pakpahan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Independent Curriculum demands synergy between national competency standards and teaching materials in schools. Although textbook reviews are frequently conducted, in-depth analysis of the quality and suitability of the General Instructional Objectives (TIU/Learning Outcomes) and Specific Instructional Objectives (TIK/Learning Objectives) in the Indonesian Language textbook for grade XI published by the Ministry of Education, Culture, Research, and Technology is still very limited. This study aims to analyze the quality (content, language, presentation) and suitability of TIU-TIK in the student textbook and teacher's guidebook entitled Smart and Smart in Indonesian Language and Literature for Senior High School Grade XI. This study uses a qualitative approach with descriptive methods through content analysis techniques. The research objects include the Student Book and the Teacher's Guidebook to see instructional consistency. The research findings show that: (1) Based on the appropriateness of the content, this textbook has high quality and is aligned with Phase F Learning Outcomes; (2) Based on the appropriateness of the language, the use of sentences is very communicative and in accordance with the thought process and cognitive development of grade XI students; (3) Based on the appropriateness of the presentation, this book contains various structural updates that facilitate the contextual integration of TIU and ICT. Overall, the Smart Smart Indonesian Language and Literature student and teacher textbooks meet quality standards and have very good conformity to curriculum objectives, so they are suitable for use as the main instrument of learning.